Desarrollo de plan operativo para la verificación estructural y operativa de equipos del centro de purificación y refinación (CEPURE) con enfoque al diseño de un manual de validación y puesta en marcha. (2023)
This project is proposed in order to carry out a validation and start-up manual for the Purification and Refining Center (CEPURE) of the Process Center for the Sustainable Industry (CEPIIS) of the Universidad de América Foundation, based on a structural validation and physics of the equipment that makes up this area. For this, factors must be taken into account that during the assembly of the units represent, in the short and/or long term, an unsafe condition when operating said equipment. In this way, there is preventive planning to carry out the start-up of the units, reducing the risk of accidents and guaranteeing the proper functioning of CEPURE. To begin with the development of this project, it is important to know about the units that will be evaluated, the CEPURE is composed of a distillation unit and a gas absorption unit, therefore, the optimal conditions for operation will be studied. expected of them, how their location should be within the pilot plant, aspects to take into account during start-up, possible failures that may occur, types of substances that should be used in the process, components of each unit (valves, sensors, controls, pipes), risks present in the equipment and safety aspects to take into account.